Analisis Penerapan Sistem Pengelolaan Aset Desa (Sipades) dalam Mewujudkan Good Governance di Desa Tanjungsari Kabupaten Sumedang - Ediyanto Ediyanto; Mona indrianie (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This research examines the Implementation of the Village Heritage Management System (SIPADES) in Realizing Good Goernance in the Village Government of Sumedang Regency. This case is interesting to study, because at this time the village has room to carry out governance. The procedure used is descriptive qualitative. There are also sources of information consisting of primary information with a total of 5 informants and secondary information with 3 various documents. The method of collecting information is tried with literature research, field research, (observation, interviews, and documents). Methods of information analysis are tried by reducing information, presenting information, as well as drawing conclusions. The results of the research are the implementation of village heritage management policies in the Tanjungsari Village Government still facing some obstacles. Among other things, in the communication aspect, there is still a lack of training and assistance in the SIPADES application. Non-human energy sources still lack.